Role of capping agents in the application of nanoparticles in biomedicine and environmental remediation: recent trends and future prospects - Javed, Rabia; Zia, Muhammad; Naz, Sania; Aisida, Samson O.; Ain, Noor ul; Ao, Qiang (Journal of nanobiotechnology, 2020)
Capping agents are of utmost importance as stabilizers that inhibit the over-growth of nanoparticles and prevent their aggregation/coagulation in colloidal synthesis. The capping ligands stabilize the interface where nanoparticles interact with their medium of preparation. Specific structural features of nanoparticles are attributed to capping on their surface. These stabilizing agents play a key role in altering the biological activities and environmental perspective. Stearic effects of capping agents adsorbed on the surface of nanoparticles are responsible for such changing physico-chemical and biological characteristics. Firstly, this novel review article introduces few frequently used capping agents in the fabrication of nanoparticles. Next, recent advancements in biomedicine and environmental remediation approaches of capped nanoparticles have been elaborated. Lastly, future directions of the huge impact of capping agents on the biological environment have been summarized.